O modelo MTSK na formação inicial de professores de matemática: o caso da disciplina de Prática Curricular I do curso de Licenciatura em Ciências - Matemática e Física. - Fonseca, Mariane Gonçalves da (Brasil, 2024)
This work stemmed from concern about the initial training of teachers in mathematics and physics, aiming to provide training that encompasses understanding didactic-pedagogical aspects. In this proposal, the Mathematics Teachers’ Specialized Knowledge - MTSK model is presented, whose structure includes important criteria for the consolidation of the mathematics education professional. Thus, the general objective of this work is to investigate the consolidation of the knowledge necessary to teach mathematics in Middle School II in the training of Mathematics and Physics undergraduates using the MTSK model. The methodological procedures were qualitative, following the studies of Fontelles et al (2009), and it emphasizes the classification of this research. The results indicate that this model contributes to the improvement of education quality and the professional growth of future teachers.